The intestinal environment potentiates bacteriophage adaptation in response to phenotypic resistance in Salmonella Typhimurium - Nicolas Wenner; Anouk Bertola; Louise Larsson; Andrea Rocker; Nahimi Amare Bekele; Chris Sauerbeck; Leonardo F. Lemos Rocha; Valentin Druelle; Marco Molari; Alexander Harms; Médéric Diard (Proceedings of the National Academy of Sciences, 2025)
Heterogeneous gene expression enables the coexistence of virulent phages with populations of isogenic bacteria comprising both phenotypically phage-resistant and susceptible cells. However, the evolvability of phages and the fitness cost they impose on susceptible bacteria challenge the evolutionary stability of the coexistence. Understanding this dynamic is critical for predicting phage–bacteria coevolution with implications for phage therapy, where resistance hinders treatment success. To address this point, we built on the discovery that heterogeneously expressed alterations of the O-antigen (phase variation) enable phenotypic resistance in Salmonella Typhimurium ( S .Tm) against the T5-like phage 37 (Φ37). We observed that phase variation allowed prolonged phage–bacteria coexistence in liquid medium. In contrast, phase variation only delayed the fixation of genetically phage-resistant S .Tm mutants when the phage–bacteria interaction took place in the gut of infected mice. The emergence of evolved phages capable of infecting both phenotypically susceptible and resistant phase variants of wild-type S .Tm selected for genetically resistant S .Tm mutants. Experimental in vitro evolution in a viscous medium recapitulated the short-lived coexistence of phages with susceptible S .Tm observed in the gut. This demonstrates that conditions in the gut increase the evolvability of phages by potentiating the effect of mutations that increase the phage host range, thereby negating the protection conferred by phase variation.